Unidad biomimética de atención e investigación biomédico (2021)
The city of Bogotá, the capital of Colombia, has a high degree of development industrial, buildings and vehicles, it also has important structures ecological, such as the eastern hills, rivers and parks, which are the ecological edge of the town. The project will be carried out in the town of Chapinero in Bogotá, near the area of ​​the 45th street station and the Javeriana University, this area is known for its large number of educational institutions, commerce and businesses. This makes it in one of the busiest places in the city, there is also a constant flow of vehicles and buses in Carrera Séptima, Avenida Caracas and Carrera thirteen. The construction industry contributes to a considerable number of ecological footprint and health problems in cities due to their materials and construction.